Estradiol Differentially Regulates c-Fos after Focal Cerebral Ischemia - Rau, Shane W. (J Neurosci, 2003)
Estrogen replacement therapy enhances mood, delays cognitive decline, and reduces the risk of neurodegeneration. Our laboratory has shown previously that pretreatment with low physiological levels of estradiol protects against middle cerebral artery occlusion (MCAO)-induced brain injury during late phases of neuronal cell death. Immediate early genes (IEGs) are induced by various forms of brain injury, and their induction is known to be a critical step in programmed cell death. The current study tested the hypothesis that the ability of estradiol to reduce MCAO-induced cell death involves attenuation of expression of one or more IEGs. We examined the effects of MCAO on the temporospatial pattern of IEG expression and the modulation of this pattern by estradiol replacement. Rats were ovariectomized and treated with either vehicle or low physiological concentrations of estradiol. One week later, rats underwent MCAO and brains were collected 1, 4, 8, 16, and 24 hr later. We assessed IEG mRNAs in discrete regions of brain by RT-PCR at 24 hr. We examined expression of c-Fos mRNA and protein in greater detail using in situ hybridization and immunohistochemistry to delineate the time course and specific regions of cortex in which estradiol influenced its expression. Our results reveal that c-fos, fosB, c-jun, and junB levels were upregulated at 24 hr. Furthermore, estradiol selectively affected the expression of c-Fos mRNA and protein by attenuating the injury-induced increase in a time- and region-specific manner. Our findings strongly suggest that the ability of estradiol to protect against MCAO-induced cell death involves attenuation of c-Fos induction.